Mesoporous carbon hollow sphere with dandelion‐like radial‐hierarchy for high‐performance supercapacitors. (15th November 2021) - Kwak, Soyul; Eom, Hojong; Kang, Jihyeon; Jang, Seohyeon; Choi, Seyoung; Kwon, Ohhyun; Kim, Tae Yong; Nam, Inho
Summary: Ordered mesoporous carbons (OMCs) possess great advantages, such as large surface area, uniform pore distribution, high porosity, and physical and chemical stability. However, the monotonic and long porous channels in OMCs hinder their further application, especially in energy storage. Here, we synthesized mesoporous carbon hollow spheres (MCHSs) with a "Dual‐templating method" using dandelion‐like silica spheres (DSSs) as the template. Through the dual‐templating method, the MCHSs directly replicated the mesoporous edge of DSSs as a thick mesoporous shell but substituted the clogged central core with hollow‐core. The combined structure with mesoporous carbon spheres and hollow‐core has various advantages over conventional OMCs. The radial and hierarchical pores in the sphere provide a large surface area (1319 m 2 g −1 ), short diffusion path, and open‐pore that facilitates ion transfer to any direction. Simultaneously, the hollow sphere carved in the center of the MCHSs allows space for the improvement of ion mobility and electrolyte retention. Also, the dense structure of the MCHSs allows more compact packing and high tap density when MCHSs were applied as an electrode. The MCHSs exhibit high specific capacitance and present a well‐developed EDLC shape at all scan rates (10 to 1000 mV s −1 ), the results show a superior electrochemical performance compared with other recent mesoporous carbon allotropes. Abstract : We synthesized mesoporous carbon hollow spheres (MCHSs) with a "Dual‐templating method." The radial and hierarchical pores in the sphere provide a large surface area, short diffusion path, and open‐pore that facilitate ion transfer to any direction. Simultaneously, the hollow sphere carved in the center of the MCHSs allows space for the improvement of ion mobility and electrolyte retention.